Human Asunder promotes dynein recruitment and centrosomal tethering to the nucleus at mitotic entry - Jodoin, Jeanne N. (The American Society for Cell Biology, 2012)
Recruitment of dynein motors to the nuclear surface is an essential step for nucleus–centrosome coupling in prophase. In cultured human cells, this dynein pool is anchored to nuclear pore complexes through RanBP2–Bicaudal D2 (BICD2) and Nup133– centromere protein F (CENP-F) networks. We previously reported that the asunder (asun) gene is required in Drosophila spermatocytes for perinuclear dynein localization and nucleus–centrosome coupling at G2/M of male meiosis. We show here that male germline expression of mammalian Asunder (ASUN) protein rescues asun flies, demonstrating evolutionary conservation of function. In cultured human cells, we find that ASUN down-regulation causes reduction of perinuclear dynein in prophase of mitosis. Additional defects after loss of ASUN include nucleus–centrosome uncoupling, abnormal spindles, and multinucleation. Coimmunoprecipitation and overlapping localization patterns of ASUN and lissencephaly 1 (LIS1), a dynein adaptor, suggest that ASUN interacts with dynein in the cytoplasm via LIS1. Our data indicate that ASUN controls dynein localization via a mechanism distinct from that of either BICD2 or CENP-F. We present a model in which ASUN promotes perinuclear enrichment of dynein at G2/M that facilitates BICD2- and CENP-F-mediated anchoring of dynein to nuclear pore complexes.